A DNA-based nanodevice for near-infrared light-controlled drug release and bioimaging. (February 2023) - Liu, Qing; Cheng, Hong-Bo; Ma, Rui; Yu, Mingming; Huang, Yuanyu; Li, Lele; Zhao, Jian
Abstract: DNA-based nanostructures have shown curative potential in drug delivery and anti-tumor therapy. However, the applications of such systems are limited by the lack of precise control over the space and duration of drug release. Here, we report a near-infrared (NIR) light-guided DNA nanodevice that enables controlled drug release for precise tumor imaging and therapy. The DNA nanodevice is constructed by engineering GC-rich DNA duplexes with an ultraviolet (UV) light labile moiety and further modification onto the surface of upconversion nanoparticles (UCNPs). The chemotherapeutic drug (doxorubicin, Dox) is intercalated into the GC motif of DNA duplexes, where the fluorescence signal of Dox is markedly quenched. Upon NIR light irradiation, the UCNPs acting as energy transducers emit UV light that can break the photolabile moiety in DNA duplexes, resulting in the controlled release of Dox and recovery of their fluorescence signal. We present that this DNA nanodevice is not only able to selectively induce tumor cells apoptosis via NIR light-mediated activation, but also enables in situ imaging and monitoring of drug release. Therefore, this modular strategy opens a window for remotely controlled drug delivery. Graphical Abstract: ga1 Highlights: ● We reported a near-infrared (NIR) light-controlled DNA nanodevice for spatiotemporally controlled drug release. ● The NIR light-responsive system could efficiently image tumor cells and inhibit tumor cells proliferation. ● This strategy opens a door for precise control of drug delivery, which may offer a route for tumor imaging and therapy.